2017
DOI: 10.21037/jtd.2017.08.122
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections after lung resection: a prospective study of risk factors in 1,091 consecutive patients

Abstract: Background: To assess incidence and risk factors of surgical site infections (SSI) (wound infection, pneumonia, empyema) in a monocentric series of patients undergoing lung resection over a decade. Methods: All patients undergoing lung resection at our institution in 2006-2015 [wedge resection, n=579; lobectomy, n=472 (12% after chemo/radiotherapy); pneumonectomy, n=40 (47% after chemo/radiotherapy)], were prospectively enrolled. Perioperative SSI risk factors were recorded: age, gender, blood haemoglobin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
5
17
1
1
Order By: Relevance
“…Previous studies have identified different, independent risk factors for SSI, also including patients' characteristics, procedures during hospitalization and characteristics depends of thoracic surgery procedure [1][2][3][4][5]. In the present study multivariate logistic regression analysis identified five independent risk factors associated with SSI: wound microbiology contamination, ASA score, duration of pleural drainage, age, and duration of operation.…”
Section: Risk Factors For Ssimentioning
confidence: 61%
See 3 more Smart Citations
“…Previous studies have identified different, independent risk factors for SSI, also including patients' characteristics, procedures during hospitalization and characteristics depends of thoracic surgery procedure [1][2][3][4][5]. In the present study multivariate logistic regression analysis identified five independent risk factors associated with SSI: wound microbiology contamination, ASA score, duration of pleural drainage, age, and duration of operation.…”
Section: Risk Factors For Ssimentioning
confidence: 61%
“…The lobectomy was the most common operative procedure performed in our patients, accounting for 944 (28.0%) of the studied operative procedures with SSI IR of 7.7%. During open lobectomy, Imperatori et al reported IR of SSI of 17.0%, IR of wound infection of 3.9% and IR of empyema of 3.2% in period 2006-2015 [1]. These differences could be explained by the fact that the authors from Italy were calculating IR of lobectomy and bilobectomy together/combined, and in our study, we were calculating IR of lobectomy and bilobectomy separately.…”
Section: Incidence Rate Of Ssi and Hapmentioning
confidence: 61%
See 2 more Smart Citations
“…Adequate Perioperative Use of Antibiotics in Thoracic Surgery Einleitung Neben dem postoperativen Wundinfekt und dem Pleuraempyem gilt die postoperative Pneumonie als eine schwere Komplikation nach lungenresezierenden Eingriffen [1]. In einer aktuellen prospektiven Studie entwickelten 22,5 % der Patienten nach Pneumektomie eine postoperative Pneumonie mit einer Mortalität von 5 % [2]. Als Risikofaktoren hierfür sind u. a. chronische Lungenerkrankungen, Übergewicht, hohes postoperatives Schmerzniveau und eine bakterielle Kolonisation des Tracheobronchialsystems beschrieben [3 -5].…”
Section: Rationale Perioperative Antibiotikatherapie In Der Thoraxchiunclassified